Hepatitis infection:a retrospective analysis of patients at Chris Hani baragwanath academic hospital,South Africa - Abuelhassan, Wamda (My University, 2019)
Background: Hepatitis C is a viral infection that leads to chronic liver disease resulting in significant morbidity and mortality. This study aimed to describe the demographics and clinical presentation of patients with chronic hepatitis C infection. Aspartate transaminase-to-platelet ratio index (APRI) and fibrosis index based-on-4-factors (FIB4) were assessed for prediction of liver fibrosis. Methods: We retrospectively reviewed 87 patients who presented to the Liver Clinic, Division of Gastroenterology, Chris Hani Baragwanath Academic Hospital from January 2007 to December 2016. Patients’ records were reviewed and analysed. Convenience sampling was used. Results: The patients’ age was 52.6(12.3) years, mean(SD). Fifty-four percent were females. Genotype 5 was exclusively found in blacks (P=<0.001) constituting 53.5% of infections in this ethnic group and 44% of the cohort, followed by genotype 1 (18.4%), genotype 3 (13.8%), genotype 4 (9.2%) and mixed-genotype infections which was 3.4%. Genotype 5 patients were older (mean age 56.7(9.8) years) than genotype 1 (46.3(11.4)) years and genotype 3 (42 (9.8)) years (P=0.002 and <0.001 respectively). The Receiver Operating Characteristic curve (ROC curve) for Metavir F0 and (APRI) (cut off <0.7) showed a moderate correlation with an AUC of 0.349 (P=0.002), sensitivity of 78.8%, specificity of 70.6% and a negative predictive value (NPV) of 63.2%. Metavir F4 vs APRI (cut off ≥1.5) showed an AUC = 0.881 (P=0.001) with sensitivity of 85.7%, specificity of 93% and a positive predictive value (PPV) of 67 %. Metavir F0 vs (FIB 4) (cut off <1.45) showed moderate correlation with AUC = 0.332 (P=0.021), sensitivity of 78.3%, specificity of 53.8% and a negative predictive value (NPV) of 73.7 %. Metavir F4 vs FIB 4 (cut off >3.25) had a strong correlation with AUC= 0.952 (P=<0.001), sensitivity of 63.6%, specificity of 100% and PPV of 100 %. Twelve-week EVR was found to predict sustained virological response to therapy (OR=27.8, 95% CI=2.8-274.3, P= 0.004). Conclusion: Genotype 5 is predominant in this cohort particularly in older age groups compared to other genotypes. Moreover, APRI and FIB4 scores were powered enough to diagnose advanced fibrosis among HCV patients. Finally, early virological response during therapy was found to determine sustained virological response.
A research report submitted to the University of Witwatersrand, Johannesburg, in fulfilment for the requirement of the degree of Master of Medicine